Kurikulum Merdeka: Optimization of Personal Abilities and Digital Literacy of Prospective Biology Teachers through Microteaching Practices - Nawawi, Nawawi; Sari, Mustika (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2024)
Kurikulum Merdeka has changed the paradigm of education in Indonesia which requires prospective biology teachers, to have better personal abilities and digital literacy. This study aims to evaluate the effect of microteaching practices on the personal abilities of prospective biology teachers and digital literacy. This research uses qualitative methods, with purposive samples, where the samples used are eight prospective Biology teacher students from the Biology Education Study Program IKIP PGRI Pontianak for the 2022/2023 academic year who attended Microteaching lectures. The assessment is carried out in three stages, namely evaluation of lesson plan, evaluation of microteaching implementation, and evaluation of personal competence and digital literacy during microteaching. In addition, an assessment of students' digital literacy skills was also carried out. The research results showed an increase in the personal abilities of each prospective biology teacher student in planning learning according to the Kurikulum Merdeka format. Personal abilities can also be reflected in dressing, speaking, and behaving as a professional teacher. The results of the digital literacy assessment show that students have excellent abilities in utilizing digital technology for learning. The practice of microteaching has a significant influence on the personal abilities and digital literacy of prospective Biology teachers.